The Multilateral System of Payments : Keynes, Convertibility, and the Internationa Monetary Fund's Articles of Agreement - Gold, Joseph (Occasional Papers; Occasional Paper ;, 1981)
Volume 26 of the Collected Writings of John Maynard Keynes records for the first time a strange episode in the development of the International Monetary Fund.